Investigating the microwave heating behaviour of pyrrhotite tailings. (15th January 2020) - Goldbaum, M.W.; Elliott, R.; Forster, J.; Maham, Y.; Bobicki, E.R.
Highlights: Pyrrhotite heats very well upon microwave exposure. Pyrrhotite permittivities increase rapidly with temperature then decline above 850 °C. Microwave heating behaviour was not correlated with pyrrhotite type. Removal of silicates by flotation had little impact on heating behaviour. Ni content appears to have influenced the microwave heating of Po tailings. Abstract: Current practice is for pyrrhotite to be rejected from conventional nickel sulphide processing circuits due to its low concentration of nickel and high sulphur content. However, the nickel content of pyrrhotite tailings (up to 1 wt.% Ni) represents a significant resource, and a new flowsheet, based on the microwave heating of pyrrhotite tailings to produce FeNi and FeS phases is under development. The microwave heating properties of pyrrhotite tailings are explored in this paper through microwave heating and permittivity tests. Thermogravimetric analysis and differential scanning calorimetry were also performed to interpret the permittivity data, and the distribution of phases within the microwave treated material was investigated by scanning electron microscopy. In general, pyrrhotite heats very well upon exposure to microwave radiation. The mass loss appears to be governed by the sulphur content and the extent of heating seems to be influenced by the Ni content. The removal of silicate impurities by froth flotation had little impact on the heating behaviour.